Legal Authority and Protection for Anesthesia Practitioners Working Without Direct Anesthesiologist Supervision in Indonesian Hospitals - Negoro, Widigdo Rekso (JUKEJ : Jurnal Kesehatan Jompa, 2025)
This study analyzes the legal authority and protection of anesthesia practitioners (penata anestesi) who provide services in hospitals without direct supervision from anesthesiologists. The issue arises from the gap between legal norms and healthcare conditions in Indonesia, particularly the unequal distribution of anesthesiologists, which creates legal challenges for practitioners in underserved regions. This research aims to assess the alignment between existing legal frameworks and actual clinical practices and to propose regulatory adjustments that strengthen legal certainty and professional protection. Using a normative juridical approach with a descriptive-analytical method, the study reviews statutory regulations, legal doctrines, and relevant literature. Qualitative analysis was conducted to examine the relationship between legal provisions and the realities of anesthesia practice. The findings show that Minister of Health Regulation No. 18 of 2016 remains restrictive and does not accommodate the limited availability of anesthesiologists. In emergencies, anesthesia practitioners may perform tasks beyond their formal authority, exposing them to potential legal liabilities. The mismatch between legal norms and practical needs results in insufficient legal protection and uncertainty in practice. This study highlights the need for adaptive, competence-based, and patient-safety-oriented regulatory reform.